Sporting shades of green: a comparative analysis of sponsored national mythmaking in Irish rugby and soccer. Issue 7 (3rd July 2017) - O'Boyle, Neil; Kearns, Colm
Abstract: This paper derives from an ongoing study of how modern sports contribute to the (re)definition of national identities in the context of increasing marketization and mediatization of sport at different levels. In this paper, we examine the symbolic tensions surrounding Three Ireland's concurrent sponsorship of the Irish international football and rugby union teams via an analysis of two television commercials commissioned by the sponsor. We suggest that although different signifiers of Irish identity are employed in the football and rugby commercials examined – and that each ostensibly represents a different 'version' of Irish identity – both campaigns draw largely from a common fund of cultural authenticity. Our analysis suggests that Three Ireland has constructed broad texts that comfortably accommodate differing signifiers of Irish identity and that permit the sponsor to trade in limited and controllable degrees of cultural difference. More broadly, our paper demonstrates how national identity can function as a 'multi-directional symbol'.